Risk Assessment of Solar Power Plant Development in Indonesia Using The Analytic Hierarchy Process Method - Ginting, Frederick Sakaja; Garniwa, Iwa (International Journal of Electrical, Computer, and Biomedical Engineering, 2025)
The Ministry of Energy and Mineral Resources is committed to building Solar Power Plant in Indonesia with the aim of increasing the national electrification ratio and ensuring equitable energy access, especially for people who have not enjoyed electricity. This study aims to determine what risk factors exist in the construction of Solar Power Plant and conduct a risk assessment using the Analytic Hierarchy Process (AHP) method. The results of the analysis show that there are 7 criteria and 38 risk sub-criteria. The project risk criterion has the highest weight with an expert value of 25.2%, self-assessment 36.9% and employees 2.2%. In the sub-criteria, the provider is late in completing the work, it has the highest weight with an expert value of 6.7%, self-assessment 10.6% and employees 0.1%.